The Scandinavian Corps in the Second Anglo-Boer War (Historia, 2021)
The short-lived Scandinavian Corps, like so much else in the annals of the Second Anglo-Boer, was unquestionably of little military significance, yet it nevertheless merits scholarly attention as an expression of minorities within certain European immigrant groups who felt strongly enough about the republican cause to risk, and iv.in many cases, lose, their lives for it. In terms of their varied and inconsistent attitudes towards the Boers and British alike, as well as their accounts of their lives as combatants and prisoners, the Nordic pro-Boers left their mark on the ethnic and military history of the pluralistic society of which they chose to be a part. The Scandinavians in question entered the war from an oblique angle, and their saga is thus but one of the many perspectives which must be included in historians' ever-widening perception of that conflict.
Keywords: Scandinavian Corps; Nordic pro-Boers; Anglo-Boer War II; Uitlanders; Military history